Pengaruh Science Comic terhadap Hasil Belajar Siswa - Desi Kurniawati; Ismul Mauludin Al Habib; Dwi Sucianingtyas Sukamto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This research aims to determine the content of comic science on the learning outcomes of class VIII students on human circulatory system material in SMP Negeri 7 Jember. The design of this study is Nonequivalent Control Group Design. The sampling technique in this research was purposive sampling technique. The sample chosen by the researcher was class VIII D as the experimental class, 37 students and class VIII E as the physical control class of 35 students. The instrument of this research is a test using 10 valid questions. The technique of analyzing the experimental and class classes using non-parametric statistical tests, namely the Wilcoxon test which is calculated by the SPSS 24 application, obtained a significance of 0.00 less than 0.05. The average score of post-test in experimental class was 85.37 out of 37 students while in the control class was 69 out of 35 students. The average N-gain results was 0.77 from 37 students in the experimental class and in the control class was 0.69 from 35 students. From the results of the study, it can be concluded that science comic influences the learning outcomes of eighth grade students on human circulatory system material in SMP Negeri 7 Jember. Keywords: knowledge comics, learning outcomes, circulatory system